Pete the Cat's Mars mission - Dean, Kim, 1969-; Dean, James, 1957- (Pete the cat., 2025)
"Marty is stuck on Mars, and it's up to Pete the Cat to rescue him! Will Pete have the tools he needs to get Marty home? Find out in this Level 1 I Can Read book complete with original illustrations from the creators of Pete the Cat, Kimberly and James Dean. Pete the Cat's Mars Mission is perfect for children learning to sound out words and sentences. Whether shared at home or in a classroom, the short sentences, familiar words, and simple concepts of Level One books support success for children eager to start reading on their own"--